Validation of the predictive equation for spatial brightness in an experimental space - Yu, Hanui; Ko, Byoungwoo; Koga, Takaaki; Hirate, Kotaroh; Suzuki, Naoyuki (Architectural Science Review, 2019)
A predictive equation for spatial brightness that is more accurate and simpler than other similar equations owing to its use of the 'arithmetic average luminance of the evaluation range' and 'standard deviation of the log-luminance' to evaluate the brightness was previously proposed by Ko et al. Although this equation has proven to be highly accurate thus far, it was derived from the results of the artificial luminance distribution by screen image experiments and requires further investigation to determine its applicability in real, natural luminance distribution by lighting of spaces. Therefore, the practical usability of this equation was examined in this study by conducting an experiment in which subjects evaluated the brightnesses of real spaces with various types of lighting. Experiments were performed by adjusting the experimental box to the same brightness after the subject observed the experimental space. The high correlation between the predicted and perceived brightnesses demonstrated the value of using the equation for evaluating spatial brightness. In addition, comparison of the results obtained using the equation and previous evaluation methods with the experimental data collected in a different real indoor space confirmed that the equation has the same explanatory power as the other evaluation methods.